2014
DOI: 10.1590/s1679-78252014000500009
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on seismic response of self-centring precast segmental columns at different post-tensioning forces

Abstract: Precast bridge columns have shown increasing demand over the past few years due to the advantages of such columns when compared against conventional bridge columns, particularly due to the fact that precast bridge columns can be constructed off site and erected in a short period of time. The present study analytically investigates the behaviour of self-centring precast segmental bridge columns under nonlinear-static and pseudo-dynamic loading at different prestressing strand levels. Self-centring segmental col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Basic models are established in ABAQUS (6.14, DASSAULT SIMULIA, France). The steel is simulated via various elastoplastic models [ 20 ]. The ideal elastoplastic model is for the stress–strain relationship of the energy dissipation elements, steel pipes, and prestressing tendons, which can be expressed as follows: where:…”
Section: Numerical Simulation and Experimental Verification Of Segmen...mentioning
confidence: 99%
“…Basic models are established in ABAQUS (6.14, DASSAULT SIMULIA, France). The steel is simulated via various elastoplastic models [ 20 ]. The ideal elastoplastic model is for the stress–strain relationship of the energy dissipation elements, steel pipes, and prestressing tendons, which can be expressed as follows: where:…”
Section: Numerical Simulation and Experimental Verification Of Segmen...mentioning
confidence: 99%
“…Multiple segmented precast columns have been investigated by other researchers such as [12][13][14][15][16][17]. In the current research presented in this chapter, this type of bridge column is investigated.…”
Section: Earthquakes -Tectonics Hazard and Risk Mitigationmentioning
confidence: 99%
“…Previous studies on the seismic performance of segmental columns normally included experimental tests (Billington and Yoon, 2004; Chou and Chen, 2006; Ou et al, 2009) and numerical simulations (Dawood et al, 2011; Nikbakht et al, 2014). These studies revealed that some factors affect the performance of segmental columns.…”
Section: Introductionmentioning
confidence: 99%